Hot or Not: Response Inhibition Reduces the Hedonic Value and Motivational Incentive of Sexual Stimuli - Ferrey, Anne E.; Frischen, Alexandra; Fenske, Mark J. (Frontiers in Psychology, 2012)
The motivational incentive of reward-related stimuli can become so salient that it drives behavior at the cost of other needs. Here we show that response inhibition applied during a Go/No-go task not only impacts hedonic evaluations but also reduces the behavioral incentive of motivationally-relevant stimuli. We first examined the impact of response inhibition on the hedonic value of sex stimuli associated with strong behavioral-approach responses (Experiment 1). Sexually-appealing and non-appealing images were both rated as less attractive when previously encountered as No-go (inhibited) than as Go (non-inhibited) items. We then discovered that inhibition reduces the motivational incentive of sexual appealing stimuli (Experiment 2). Prior Go/No-go status affected the number of key-presses by heterosexual males to view erotic-female (sexually-appealing) but not erotic-male or scrambled-control (non-appealing) images. These findings may provide an important foundation for developing inhibition-based interventions to reduce the hedonic value and motivational incentive of stimuli associated with disorders of self-control.